การศึกษากระบวนการถ่ายทอดการบรรเลงแคนลายแม่บทของครูสมบัติ สิมหล้า - สราวุฒิ สีหาโคตร (จุฬาลงกรณ์มหาวิทยาลัย, 2014)
This research aims to 1) study the transmission process of the six primary songs of the Khaen including Lai Yai, Lai Noi, Lai Soudsanaen, Lai Po Sai, Lai Say, and Lai Soi and 2) develop a teaching manual for the six primary modesof the Khaen in accordance with the teachings of Sombat Simlah. This study uses a qualitative research methodology through data collection in the form of in-depth interviews. The data is analyzed by using an interpretive method and inductive reasoning approach and presented in a descriptive manner. The findings firstly suggest that Sombat Simlah acquired his skills in playing and teaching the six primary modes of Khaen through receiving intensive training from his father and various Khaen artists. His students are divided into three categories as 1) those with the basic skills in performing primary modes 2) those with the basic skills to play Khaen but have no prior basic skills to its primary modes and 3) those who have no basic skills to play Khaen. His two methods of teaching the primary modes comprise of a one-on-one session and in playing the pieces of Mor Lam music. Sombat Simlah teaches at home in a traditional manner and at universities where he is invited. His four principles of teachings are based on the level of the student, the method of playing, the compositions, and the step-by-step technique where he uses oral transmission to explain and demonstrate so students understand and are able to perform correctly. Sombat Simlah gives the highest focus on creating diverse and sharp sounds and techniques for the audience’s pleasure. Secondly, the teaching manual on the primary songs of the Khaen by Sombat Simlah consists of the manual information, contents, teaching and training methods on the primary modes of the Khaen, assessment and evaluation, and references.